Prevalensi kasus dehidrasi pada mahasiswa Universitas Gadjah Mada - Mirza Hapsari Sakti Titis Penggalih; Zaenal Mutaqien Sofro; Eka Roshifita Rizqi; Yuniko Fajri (Jurnal Gizi Klinik Indonesia, 2014)
Background: Involuntary dehydration can lead to body function of disturbances. Orthostatic measurements were performed to determine the involuntary dehydration caused by orthostatic hypotension. Dehydration is also influenced by the high level of activity and ambient temperature without sufficient fluid intake. Students are prone to dehydration due to their activity, they have to be well hydrated to achieve their academic and nonacademic performances.Objective: To determine the prevalence of dehydration among students of Gadjah Mada University.Method: An observational study with the cross-sectional design were conducted and involved 274 students of Gadjah Mada University. Orthostatic measurement and interview of their activity and smoking habit were performed on all subjects.Results: The prevalence of dehydration were 60.9%. Type of activity and smoking habit did not affect the hydration status.Conclusion: Dehydration prevalence rate is still high on the students. As almost all students are dehydrated, then the factors that should be able to distinguish the condition of dehydration such as a type of activity and smoking habit, seems to give no effect in this study.